Tumor Reduction with Pazopanib in a Patient with Recurrent Lumbar Chordoma - Maurício Fernando Silva Almeida Ribeiro; Micelange Carvalho de Sousa; Samir Abdallah Hanna; Marcos Vinicius Calfat Maldaun; Ceci Obara Kurimori; Luiz Guilherme Cernaglia Aureliano de Lima; Romulo Loss Mattedi; Rodrigo Ramella Munhoz (Case Reports in Oncological Medicine)
Introduction. Chordomas are rare malignancies of bone origin that occur in the axial skeleton, typically the skull base and lumbar/sacral regions. Although often classified as low-grade neoplasms, its locally infiltrative behavior may result in significant morbidity and mortality. Optimal surgical resection may be curative, but up to 50% of the cases relapse within 5 years, and currently there are no systemic treatments approved in this setting. A large proportion of these tumors express stem-cell factor receptor (c-KIT) and platelet-derived growth factor receptors (PDGFRs), providing a rationale for the use of tyrosine-kinase inhibitors (TKIs). Case report. A 27-year-old male presented with recurrent chordoma of the lumbar spine 4 years after initial diagnosis. Salvage therapies in the interval included repeat resections and radiation therapy. He ultimately developed multifocal recurrence not amenable to complete excision or reirradiation. A comprehensive genomic profiling assay was performed and revealed nondrugable alterations. Decision was made to proceed with systemic treatment with pazopanib 800 mg/day, resulting in tumor reduction (−23.1% reduction in size) and prolonged disease control. Conclusion. For this patient with a multiple recurrent chordoma and limited treatment options, pazopanib resulted in sustained clinical benefit following initial tumor reduction.